198 new elite multi-purpose barley genotypes for food, feed, forage, and malt shared with Indian Institute of Wheat and Barley Research (IIWBR) for multi-location testing - CGIAR Research Program on Livestock (2020)
The elite genotypes have been shared with IIWBR that will multiply seeds and share them with research institutes in India for validation and potential national/regional release.